Iron Homeostasis as a Mediator Linking Central Obesity with MASLD and Primary Liver Cancer: A Two-Step Mendelian Randomization Study - Yuping Zeng; Xia Wang; Shenlin Liao; Chuan Li; Jie Chen; He He (Biomedicines)
Objectives: This study aimed to explore the mediating effects of iron homeostasis biomarkers linking central obesity with metabolic dysfunction-associated steatotic liver disease (MASLD) and primary liver cancer (PLC) via Mendelian randomization (MR) analysis. Methods: Two-sample bidirectional MR, multivariable MR, and mediation analyses were used to investigate the causal associations among obesity-related traits, iron homeostasis biomarkers, MASLD, and PLC. For the discovery and replication analyses, GWAS summary data for iron homeostasis biomarkers, MASLD, and PLC were extracted from two datasets, and the combined effects were pooled to corroborate the conclusions. Results: BMI and waist circumference were associated with a risk of MASLD in their combined effects (OR = 1.83, 95% CI = 1.33–2.52 for BMI; OR = 1.98, 95% CI = 1.63–2.41 for waist circumference). Waist circumference but not BMI had significant causal effects on the risk of PLC in the discovery dataset (OR = 1.71, 95% CI = 1.01–2.89 for BMI; OR = 2.72, 95% CI = 1.37–5.39 for waist circumference). In both of the iron homeostasis datasets, genetically predicted increased ferritin was associated with increased risk of MASLD by multivariable MR. We only observed that genetic liability to increased ferritin was associated with increased risk of PLC in iron homeostasis dataset 1 after adjusting for waist circumference. By two-step MR analysis, we found that genetic liability to ferritin mediated 3.34% (95% CI: 0.17–8.08%) of waist circumference effects on MASLD risk and 18.84% (95% CI: 3.01–40.51%) of its effects on PLC risk. Conclusions: Waist circumference and iron homeostasis biomarkers were causally associated with increased risks of MASLD and PLC. Central obesity may contribute to the development of MASLD and PLC by increasing ferritin levels.